Collaborative research in multilingual classrooms - Denos, Corey Hawes, 1946- (Critical language and literacy studies, 2009)
Reporting on the research collaborations of a group of teachers, graduate students and a university professor, this book weaves together their collective insights about how classrooms might be better for students of diverse linguistic and cultural backgrounds, abilities and socio-economic circumstances, and better for teachers as well.